POLITIK HUKUM: PERUMUSAN KEBIJAKAN PERLINDUNGAN TENAGA KERJA DAN PENANAMAN MODAL (STUDI PADA KOTA BATAM) - Safitri, Dian Prima; Sucipta, Pery Rahendra (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2018)
The demand for devolution of authority from the central government to local governments has caused the regional autonomy system, especially the economic growth to be very important. The geographical condition of Batam City which is very strategic and the special status of the Free Trade Zone that should provide a very large contribution to investment. Among the desire to increase the rate of investment sourced both domestically and abroad, the government was negligent towards the protection of labor. The undesirable impact is the unilateral termination of employment, followed by an escaping and irresponsible company. The research method used is normative and empirical juridical. Theoretically, the type of investment, institutions and processes should be able to explain accompanied by labor protection laws. Various similar cases have so far not been resolved by the government. This is supported by formal legal policies that have not been formulated in Batam City which have special conditions that are different from other regions. The existence of the Batam City Government and the Regional Concession Board must take a role in investment and labor protection.